COMPARATIVE STUDY OF VARIOUS AGRICULTURAL FINANCIAL PROVIDERS IN BANDUNG DISTRICT - Raden Trizaldi Prima Alamsyah; Eliana Wulandari; Tuti Karyani (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Capital plays a crucial role in fulfilling the production needs of agriculture. As a hub for agricultural production, farmers in Bandung District utilize various financial providers to meet their capital requirements. However, some farmers still encounter difficulties in obtaining finance. This research aims to identify the sources of finance obtained by farmers and evaluate the benefits and risks of various financial providers. A survey was applied using proportionate stratified random sampling through the distribution of questionnaires. The questionnaire consisted of questions related to the sources of finance used by the farmers and their experiences with obtaining finance. The data obtained were analyzed using descriptive statistics, which involved summarizing and organizing the data to describe various sources of financial providers in Bandung District. The study results indicate that 61% of farmers have obtained finance from various sources. The most commonly accessed source of finance is non-bank financial providers. In terms of benefits, non-bank financial providers have the highest utility and are classified as high, while digital financial providers have the highest level of effectiveness and are classified as very high. In terms of risk, bank financial providers are the safest source and are classified as low. The key to improving farmers' access to finance and ensuring the success and sustainability of their operations is effective collaboration between the government, financial institutions, and farmers themselves.